Buku pinter budaya Jawa : mutiara adiluhung orang Jawa - Endraswara, Suwardi, 1964-; Danuri (Yogyakarta : Gelombang Pasang, 2005)
Javanese culture and civilization; handbook.
Daftar pustaka : p. 367-374
Keywords: Javanese -- Social life and customs; Java (Indonesia) -- Social life and customs